Documents from and on economic thought - Samuels, Warren J., 1933- (Emerald, 2006)
This volume publishes a wide variety of documents. Included are Notes taken by Henry R. Seager in 1890; Robert Hoxie's Introductory Lecture on the nature of the history of political economy (1916) coupled with an internet discussion on the history of economic thought as the history of error (2005); two law school student papers on John R. Commons' work on law and economics (1926); Edwin R. A. Seligman's Autobiography (1929); Glenn Johnson's notes on Frank H. Knight's University of Chicago course on economic theory (1947) and documents pertaining to Johnson's Michigan State University course on methodology (1947); and the the conclusion of notes from Edwin E. Witte's University of Wisconsin course on government and labor (1955). It compiles hard-to-find documents into one convenient resource. Writings included span more than a century of thought.
Keywords: Business & Economics -- Economics -- General.; Economic theory & philosophy.; Economics -- Study and teaching (Higher); Economics -- Methodology.; Economics -- Research.; elektronické knihy; electronic books